Recent Progress toward Measles Elimination in Hokkaido, Japan, during 2011–2012 - Miyoshi, Masahiro; Komagome, Rika; Ishida, Setsuko; Kikuchi, Masayuki; Sato, Hiroko; Ito, Harumi; Nagano, Hideki; Okano, Motohiko (Japanese Journal of Infectious Diseases, 2014)
Laboratory diagnoses for measles were performed in a total of 97 cases in Hokkaido, Japan, during 2011–2012. Two patients were confirmed to be positive for measles virus (MV), both of whom lived in the Iburi district of Hokkaido. Molecular analysis of the nucleotide sequences of the nucleoprotein (N) gene revealed that these 2 strains had high homology with each other and belonged to the genotype D8. The onset interval of these cases and epidemiological data suggested that MV transmission had occurred between them and then terminated. Phylogenetic analysis of the N gene revealed that the strains identified in Hokkaido were classified into a cluster that contained many genotype D8 strains that were detected within a large area of Japan. Eventually, 9 cases were officially reported as measles. However, other than the abovementioned 2 cases, no genetic information regarding MV was obtained. In future, further active surveillance combined with the genetic investigation should be required in all suspected measles cases to verify the elimination status.